2023
DOI: 10.1001/jamanetworkopen.2023.24240
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gastroesophageal Reflux Symptoms and Sleep Quality Among Women in the Nurses’ Health Study II

Abstract: ImportanceLimited data exist on the association of gastroesophageal reflux (GER) symptoms with sleep quality.ObjectiveTo prospectively investigate the association between GER symptoms and sleep quality.Design, Setting, and ParticipantsThis prospective cohort study included data from the Nurses’ Health Study II of female nurses in the US. Participants self-reported the frequency and duration of GER symptoms beginning June 2005, with updates every 4 years through June 2015. Follow-up was completed June 2019, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is worth noting there is likely a reciprocal relationship between sleep quality and GI symptoms including nausea and abdominal pain. Patients with GI conditions tend to report poorer sleep quality than healthy controls ( 37 - 39 ). In patients with IBS, more waking episodes during sleep was predictive of more abdominal pain ( 38 ), GI distress, and worse quality of life but not bowel consistency or frequency ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting there is likely a reciprocal relationship between sleep quality and GI symptoms including nausea and abdominal pain. Patients with GI conditions tend to report poorer sleep quality than healthy controls ( 37 - 39 ). In patients with IBS, more waking episodes during sleep was predictive of more abdominal pain ( 38 ), GI distress, and worse quality of life but not bowel consistency or frequency ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stresas. Sutrikęs miegas didina lėtinių ligų riziką [21]. Stresas taip pat neigiamai veikia GERL simptomų išsivystymą.…”
Section: Kūdikių Vaikų Ir Paauglių Gerl Rizikos Veiksniaiunclassified
“…Stresas taip pat neigiamai veikia GERL simptomų išsivystymą. Kartu su prasta miego kokybe ir kūno nuovargiu, tai ženkliai padidina GERL pasireiškimo tikimybę ar dažnesnį GERL simptomų paūmėjimą [3,21]. Išvados 1.…”
Section: Kūdikių Vaikų Ir Paauglių Gerl Rizikos Veiksniaiunclassified
“…While some studies have indicated that shift work may impact the gastrointestinal diseases of nurses (8,9), it remains debated whether this effect is related to sleep quality, as some studies suggest that this association may be independent of sleep quality (11). Concurrently, several studies have highlighted the significant impact of sleep quality on adverse gut conditions (13)(14)(15). Understanding the impact of sleep quality on adverse gut conditions is crucial, especially given the emerging interest in the gut-brain axis theory.…”
Section: Introductionmentioning
confidence: 99%